2021
DOI: 10.3390/s21196578
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Spectroscopy (EIS): Principles, Construction, and Biosensing Applications

Abstract: Electrochemical impedance spectroscopy (EIS) is a powerful technique used for the analysis of interfacial properties related to bio-recognition events occurring at the electrode surface, such as antibody–antigen recognition, substrate–enzyme interaction, or whole cell capturing. Thus, EIS could be exploited in several important biomedical diagnosis and environmental applications. However, the EIS is one of the most complex electrochemical methods, therefore, this review introduced the basic concepts and the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
311
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 604 publications
(312 citation statements)
references
References 117 publications
0
311
0
1
Order By: Relevance
“…In this regard, the use of EIS in the frequency range 100 Hz to 1 MHz allows us to work in the range corresponding to the end of the α-dispersion and a wide spectrum of the β-dispersion and, therefore, effectively identify bioimpedance differences in the samples in the studied range: (a) at lower frequencies, the capacitance of the cell membranes allows the current to flow through the extracellular fluid since the components of the layers in the cell and organelle membranes (protein, macromolecules, and other constituents) have time to polarize and thus prevent the flux of electric current through them, acting as capacitive components, an, (b) in the higher frequency range, capacitive impedance decreases, since current through the cells (tissues in intracellular fluid) improves as frequency increases, therefore diminishing the electrical resistance of the tissue [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the use of EIS in the frequency range 100 Hz to 1 MHz allows us to work in the range corresponding to the end of the α-dispersion and a wide spectrum of the β-dispersion and, therefore, effectively identify bioimpedance differences in the samples in the studied range: (a) at lower frequencies, the capacitance of the cell membranes allows the current to flow through the extracellular fluid since the components of the layers in the cell and organelle membranes (protein, macromolecules, and other constituents) have time to polarize and thus prevent the flux of electric current through them, acting as capacitive components, an, (b) in the higher frequency range, capacitive impedance decreases, since current through the cells (tissues in intracellular fluid) improves as frequency increases, therefore diminishing the electrical resistance of the tissue [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] From the electrochemical point of view, electrochemical features of the triazole and mixed triazole/metals were reported using the electrochemical impedance spectroscopy (EIS) and the cyclic voltammetry (CV) in order to identify their electrocatalytic activity along with their electron transfer. [ 21–25 ] Moreover, the docking investigation and computional studies showed the imagination of chemical and physcial properties of compounds and confirmed thier biological activities. [ 26,27 ]…”
Section: Introductionmentioning
confidence: 87%
“…It offers several advantages over other electrochemical techniques, including determining relaxation processes. Accordingly, EIS can investigate intrinsic material properties or specific processes that could affect the conductivity, resistance, and capacitance of an electrochemical system [ 139 , 140 ]. EIS can be used to study the pore sizes of porous electrodes (by employing the appropriate equivalent electrochemical circuit) [ 140 ].…”
Section: Conductive Polymers For Electrosythesized Mipsmentioning
confidence: 99%
“…Due to these properties, EIS is a very important technique to study and understand the interfacial properties related to selective molecular recognition of bioactive molecules, or even whole cells. Magar et al [ 139 ] claimed that the differences in the EIS response of the conductive polymer after the binding of the spores in the cavities (affinity sites) of the polymer were probably due to the realignment of the chains of the polymer network. These changes were also related to the proposed mechanism by which the binding of an antigen on the surface of antibody-immobilised Ppy alters the film’s conductivity.…”
Section: Conductive Polymers For Electrosythesized Mipsmentioning
confidence: 99%